Detection of Human Microchimerism following Allogeneic Cell Transplantation Using Droplet Digital PCR - Catherine A. Lombard; Alexandre Fabre; Jérôme Ambroise; Joachim Ravau; Floriane André; Nawal Jazouli; Mustapha Najimi; Xavier Stéphenne; Françoise Smets; Jean-Luc Vaerman; Etienne M. Sokal (Hindawi Limited, 2019)
Background. Cell transplantation is in clinical development for the treatment of various ailments including acquired and inborn hepatic diseases. Detection and quantification of the donor cells after infusion remain difficult. Traditional methods (sex-based FISH, HLA mismatch, and Short Tandem Repeat PCR) can only achieve low levels of sensitivity (1%) and therefore are seldom used. The use of a droplet digital PCR (ddPCR) assay based on mismatch of null alleles is a promising alternative. Methods. We selected genes with a high frequency of null genotype in the general population (SRY, RHD, TRY6, LEC3C, GSTM1, and GSTT1) and investigated their expression by liver progenitor cell donors and liver cell therapy recipients, in order to identify genes of interest for each donor/recipient couple. We first validated the detection of microchimerism by ddPCR and then used these assays to detect and quantify microchimerism in pre- and postinfusion liver biopsies. Results. We validated the ddPCR detection of the selected genes based on linearity, precision, lack of inhibition, and accuracy, and we established limits of blank, limits of detection, and limits of quantification to ensure the reliability of the results. After genotyping donors and recipients, we were able to identify at least one gene of interest for each donor/recipient couple. We detected donor cells in the three patients posttransplantation. However, analysis of several biopsies taken at the same timepoint revealed a heterogeneous cell distribution. In addition, the values obtained remained below the limit of quantification. Therefore, the actual quantification of microchimerism may not be entirely accurate. Conclusions. Overall, our study demonstrates that the detection of microchimerism post-liver cell transplantation can be performed using ddPCR amplification of null allele genes expressed by the donor but absent from the recipient. However, this technique can be extended to other cell types and target organs in cell transplantation.